Assessing the spatial relationships between mining and land degradation: evidence from Ghana - Moomen, Abdul; Dewan, Ashraf (Taylor & Francis, 2016)
© 2016. Informa UK Limited. The relationships between mining and land degradation, their potential socioeconomic impacts and extents were quantified and analysed in this study. A case study was conducted in the Upper West, which is an emerging mining region in Ghana. Land cover, socio-economic and monthly rainfall data were used in GIS. Mining-induced land degradation indices range from 0.02 to 0.80. The Fournier co-efficient model was used to obtain erosivity indices between 42 and 84 mm, bringing mining concessions into severe erosivity zones. The results of this study will facilitate a concerted effort by governments and companies to prioritise sustainable mining and rural development.